Frustration and hydrophobicity interplay in protein folding and protein evolution - Oliveira, Leandro C.; Silva, Ricardo T. H.; Leite, Vitor Barbanti Pereira; Chahine, Jorge (American Institute of Physics (AIP), 2006)
A lattice model is used to study mutations and compacting effects on protein folding rates and folding temperature. In the context of protein evolution, we address the question regarding the best scenario for a polypeptide chain to fold: either a fast nonspecific collapse followed by a slow rearrangement to form the native structure or a specific collapse from the unfolded state with the simultaneous formation of the native state. This question is investigated for optimized sequences, whose native state has no frustrated contacts between monomers, and also for mutated sequences, whose native state has some degree of frustration. It is found that the best scenario for folding may depend on the amount of frustration of the native structure. The implication of this result on protein evolution is discussed. (c) 2006 American Institute of Physics.